Power to the people? The impact of decentralization on governance - Axel Dreher (ETH Zurich, KOF Swiss Economic Institute, 2006)
The paper analyzes the impact of decentralization on governance employing four indicators of governance and five measures of decentralization. Depending on data availability, crosssections for a maximum of 129 countries are estimated. Results for a panel of about 70 countries over the period 1984-2001 are also presented. The results show that decentralization - measured as the share of sub-national employment, revenues or, respectively, expenditures - improves governance. This is particularly true for low income countries but - depending on the indicator employed - to some extent for high income countries also. However, the number of sub-national government tiers exerts a negative impact on some dimensions of governance.
Keywords: H40; H71; H72; H77; 330; Decentralization; Governance; Legal Quality; Judicial Independence; Federalism; Institutions; Dezentralisierung; Föderalismus; Governance-Ansatz